From Subsidies to Loans: The Effects of a National Student Finance Reform on the Choices of Secondary School Students - Alexandra de Gendre; Jan Kabátek (Institute of Labor Economics (IZA), 2021)
We analyse the effects of a national student finance reform in the Netherlands, which replaced universal subsidies for higher education students by low-interest loans. We show that this reform had a large impact on education choices of secondary school students, lowering their enrolments in college-preparing tracks and increasing the share of students specializing in STEM subjects. The reform also affected the living arrangements of new college entrants. Our findings highlight that secondary school students respond to the modes of higher education financing well ahead of their graduation, and that financial aid uncertainty alone can deter many from pursuing higher education.
Keywords: 22; I23; I24; 330; Netherlands; higher education; student finance; financial aid; policy uncertainty